Electrohydrodynamic processing for the production of zein-based micro- and nanostructures - Silva, Pedro Miguel Peixoto (2021)
Recently, plant derived proteins have increased in interest and use due to a combination of interesting properties and industry-wide trends to replace animal derived proteins. Electrohydrodynamic processing (EHDP), can be used to develop micro- and nanostructures of plant proteins in a facile manner and, thus, increase their opportunities in the food, pharmaceutical, and biomedical industries. One of the most currently studied and promising plant proteins is zein. This review covers the most studied strategies to produce electrospun and electrosprayed zein-based structures. The most relevant properties, such as size, morphology, and surface area, are discussed according to the potential areas of interest, for instance in the food, biomedical, and pharmaceutical industries. In addition, applications of other electrospun/electrosprayed plant derived proteins are also presented, confirming the increasing interest of different industries in alternative proteins which can help promote sustainability.